Beyond Human Rights Education: Re-Imagining Sociality for Participatory Striving - Krause, Sabine; Zahnd, Raphael; Veck, Wayne; Proyer, Michelle; Koenig, Oliver; Hanková, Magdalena (Journal of Contemporary Issues in Education, 2025)
This article presents a theoretical elaboration based on the thesis that the UN Declaration on Human Rights (UNDHR) is not sufficient to realize co-creative practices for a (world) society based on the principles of diversity, equity, inclusion, and justice. We argue that these goals are not a legal but a social task and responsibility rooted in a deeply social concern. In addressing the difficult implementation of UNDHR, the article turns to notions of the fellow human being and relatedness as the foundation of a society. Philosophical concepts and anthropological perspectives are used to demonstrate how education as “coming into practice” (Biesta, 2006) plays a central role in preparing individuals for sociality, understood as a way of getting to know different worlds, seeking diversity, striving for understandings, and finding connections to oneself by embracing “otherness.”